(untitled) (Communications in Computational Physics, 2020)
Acupuncture has been in clinical practice in China for thousands of years and its analgesia effect is worldwide accepted. However, the mechanism of acupuncture effect is not well understood. The study focuses on signaling pathways induced by acupuncture, analyzes the cooperative action of the acupoints' structure and the associated chemical mediators during acupuncture, establishes a mathematical model clarifying the roadmap of electroneurographic signal startup and transmission mechanism induced by acupuncture, quantitatively analyzing the response in acupoints to acupuncture. These work contributes to reveal the activation and transmission mechanism of neural signals induced by acupuncture from systems biology perspective, lays the foundation for the integration of acupuncture theory and modern science and further guides the clinical treatment and experimental research of acupuncture.